(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This scientific article analyzes the genesis of the moral, ethical, and legal foundations of the judiciary institution that was formed in the ancient periods within the territory of present-day Uzbekistan. Scientific conclusions regarding the moral, ethical, and legal foundations of the judiciary have been developed